On the crab spider genus Angaeus Thorell, 1881 and its junior synonym Paraborboropactus Tang and Li, 2009 (Araneae: Thomisidae) - Benjamin, Suresh P. (Zootaxa, 2013)
Morphological comparison of the genera Angaeus Thorell, 1881 and Paraborboropactus Tang and Li, 2009 (Araneae: Thomisidae) shows that the latter should be relegated to a junior synonym of the former. Further, I propose the following new synonyms: Angaeus leucomenus (Thorell, 1895), Stephanopis weyersi Simon, 1899 and Paraborboropactus leguminaceus Tang and Li, 2009 = Angaeus rhombifer Thorell, 1890 syn. nov., Paraborboropactus oblatus Tang and Li, 2010 = Angaeus lenticulosus Simon, 1903 syn. nov. The following species are transferred from Paraborboropactus: Angaeus canalis (Tang & Li, 2010) comb. nov., Angaeus liangweii (Tang & Li, 2010) comb. nov., Angaeus rhombus (Tang & Li, 2009) comb. nov. and Angaeus zhengi (Tang & Li, 2009) comb. nov. The holotype of Angaeus pudicus (type species of the genus) is illustrated, and the male and female of Angaeus rhombifer are redescribed and illustrated based partly on fresh material from Singapore. A new species, Angaeus christae sp. nov. is described based on both sexes, and a syntype of Angaeus comatulus Simon, 1909 is illustrated.